(untitled) (Computer systems and information technologies, 2021)
This paper shows an example of the application of the method of hierarchy analysis to build a hierarchy of programming environments, which provides support for selecting the optimal programming environment for software in accordance with the requirements of the developer and user. As a result of the application of the method of hierarchy analysis, a hierarchy of programming environments for software development was built, which will be useful for building criteria and production rules for selecting a programming environment for software. The constructed hierarchy has the following form: 1) Microsoft Visual Studio (33.1%); 2) Eclipse (19.6%); 3) PhpStorm (19.2%); 4) Netbeans (17.2%); 5) PyCharm (11%). Hierarchy analysis makes it possible to determine what is the best for software development is the Microsoft Visual Studio environment, but the price of such an environment is quite high. Next and almost equal in technical capabilities are the environments Eclipse, PhpStorm, Netbeans, PyCharm